Chronic pain epidemiology from aetiology to public health - Croft, Peter, 1949 Nov. 11-; Blyth, Fiona M.; Windt, Danielle van der. (Oxford : Oxford University Press, 2010)
This text presents individual conditions as examples of chronic pain, together with chapters that provide overviews on the assessment of pain and methodological issues behind population assessment. It provides a framework and basis for thinking about chronic pain and the potential for its prevention in public health terms.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chronic pain -- Epidemiology; Chronic pain -- Prevention; Chronic pain -- Etiology